Faça-se luz: a eletrificação urbana no Cariri Cearense (1949-1972) - Gomes, Assis Daniel (2016)
With the founding of the Hydroelectric Company of São Francisco (Chesf) in 1945 some cearenses politicians saw the opportunity to energize its territory and thus promote a substantial change in its economy by strengthening its industrial activity. Intellectuals belonging to Cariri also gathered to fight for this resource for your region, they built in 1949 the Pro-Electrification Committee and Industrialization of Cariri. The objective, then, think how changed the regional and state daily in 1950. Taking into account for this, the emergence of a political dispute around two electrification projects, advances and the entrance of technological objects that It came after power in 1961, and the desire to become a modern industrialized space. To that end, there was a range of sources in order to seek traces, confront them and destroy them to erect an analysis of the construction of the Cariri Electricity Company; that moved, in turn, dreams and desires linked to past projects, emerging them again before and after its foundation. Finally, when considering the material and immaterial changes in caririenses urban spaces, there was also the presence of American culture in their daily lives - derived from the rapprochement between the US and Brazil - mainly in Cariri through its support financial and technical tied to USAID and the Project Morris Asimow.